More than a metaphor: ‘climate colonialism’ in perspective - Bhambra Gurminder K.; Newell Peter (Global Social Challenges Journal, 2022)
In early 2022, over 30 years after the Intergovernmental Panel on Climate Change (IPCC) released its first report on the challenges posed by climate change and four subsequent Assessment Reports later, the word ‘colonialism’ finally entered its official lexicon. The sixth report on ‘Impacts, Adaptation and Vulnerability’  references colonialism, not only as a historical driver of the climate crisis, but also as something that continues to exacerbate the vulnerabilities of communities to it (IPCC, 2022). As Funes (2022) argues, this comes in the wake of long-standing arguments made by Indigenous groups and others on the frontline of climate change about the centrality of colonialism to comprehending and responding to the crisis. The last decade has also seen a significant increase in scholarly literature that draws explicit links between colonialism and climate change – much of which is referenced in the latest IPCC report. While formal acknowledgement of this relationship is long overdue, in this article we argue for caution and precision in the invocation of colonialism within these debates. Following Tuck and Yang’s (2012) classic article setting out why ‘decolonization is not a metaphor’, we argue relatedly that colonialism needs to be understood as more than a metaphor in climate change debates.